Individuals Differences Considerations in Prophetical Guidance to the Companions - Mustafa, Ali Salih Ali (Journal of Islamic and Religious Studies, 2018)
The aim of this research paper is to identify the extent of advertency the Prophet (peace be on him) made to consider individual differences in educating the companions the teachings of Islam; inAvesting their potentials in serving the invitation unto Allah and spreading Islam on earth. This paper also aims to set apart Islamic perspective of individual differences from that of non-Islamic in terms of treatment and acknowledgement. A significant contribution of this paper is to illustrate the prophetical attention given to individual differences in crises management and utilizing it in rectifying modern Islamic path.